2009
DOI: 10.1083/jcb.200810137
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnts function as potent regulators of osteogenesis by human mesenchymal stem cells

Abstract: Genetic evidence indicates that Wnt signaling is critically involved in bone homeostasis. In this study, we investigated the functions of canonical Wnts on differentiation of adult multipotent human mesenchymal stem cells (hMSCs) in vitro and in vivo. We observe differential sensitivities of hMSCs to Wnt inhibition of osteogenesis versus adipogenesis, which favors osteoblastic commitment under binary in vitro differentiation conditions. Wnt inhibition of osteogenesis is associated with decreased expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
130
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 30 publications
7
130
1
1
Order By: Relevance
“…Nevertheless, even the in vivo survival of GW-treated hMSCs was transient, suggesting a support role for hMSCs where the cells transiently up-regulate angiogenesis and inherent osteogenic capacity of the host's tissue. In agreement with this observation, it has recently been demonstrated that a population of hMSCs with an enhanced endogenous canonical Wnt signaling serves to enhance synergistically the ostoegenic capacity of coadministered hMSCs with a lesser degree of Wnt signaling (25).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Nevertheless, even the in vivo survival of GW-treated hMSCs was transient, suggesting a support role for hMSCs where the cells transiently up-regulate angiogenesis and inherent osteogenic capacity of the host's tissue. In agreement with this observation, it has recently been demonstrated that a population of hMSCs with an enhanced endogenous canonical Wnt signaling serves to enhance synergistically the ostoegenic capacity of coadministered hMSCs with a lesser degree of Wnt signaling (25).…”
Section: Discussionsupporting
confidence: 59%
“…3B). It has been speculated that arrest of canonical Wnt signaling occurs during terminal differentiation of osteoprogenitor cells, and Dkk-1 has been implicated in this process (24,25). Dkk-1 secretion was reduced in all cases, with maximal inhibition occurring at concentrations that induced highest ALP activity (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Our observation that Wnt3a treatment inhibits osteogenic differentiation in mesenchymal cells (e.g., ASCs and E16) is consistent with previous in vitro studies performed on other multipotent mesenchymal cells. [41][42][43][44] In addition, our study provides also in vivo evidence complementing in vitro results. It must be pointed out that in vitro Wnt3a treatment represents a constant and continuous treatment of cells, compared to in vivo treatment where calvarial bones are initially exposed to doses of Wnt3a protein, which gradually decreased overtime.…”
Section: Discussionsupporting
confidence: 56%
“…7, B and C). There are many reports that PPARG expression is suppressed by Wnt/␤-catenin signal during osteogenesis (42,43). The Wnt/␤-catenin signal may be strongly activated in the cells cultured on the stem cell matrices and early stage matrices to inhibit PPARG expression.…”
Section: Characterization Of Stepwise Osteogenesis-mimicking Matrices-mentioning
confidence: 99%